1992
DOI: 10.1007/bf01309810
|View full text |Cite
|
Sign up to set email alerts
|

Induction of protective immunity and neutralizing antibodies to pseudorabies virus by immunization of anti-idiotypic antibodies

Abstract: Xenogenic anti-idiotypic antibodies (anti-Id) were prepared in rabbits against three murine neutralizing monoclonal antibodies (MAbs) directed to pseudorabies virus glycoproteins. These anti-Id were highly specific to idiotopes on the corresponding MAb molecules. Because the binding of MAb to the corresponding anti-Id was inhibited by the addition of viral envelope protein, these anti-Id seemed to contain a subpopulation of antibodies against the antigen-combining site (paratope) or the region related to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The most efficacious virus-neutralizing antibodies target PRV gC and gD (89, 115 164, 256, 293, 425). Subunit vaccines consisting of gC or gD, as well as anti-idiotypic anti-gD antibodies elicit some degree of protective immune responses (257,261,409). A large portion of the neutralizing activity in convalescent swine sera is directed against gC (27).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…The most efficacious virus-neutralizing antibodies target PRV gC and gD (89, 115 164, 256, 293, 425). Subunit vaccines consisting of gC or gD, as well as anti-idiotypic anti-gD antibodies elicit some degree of protective immune responses (257,261,409). A large portion of the neutralizing activity in convalescent swine sera is directed against gC (27).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…It was interesting to note that both RAb2-B1 and RAb2-B2 reacted strongly with M1877 ( Fig. 2, b response to the original antigen, which has been demonstrated in numerous antibody systems (5,7,8,14,15,17,21,22,24,25,28,29). Our observation that immunization of mice with RAb2-A induced an anti-VP7 antibody response further supports the conclusion that RAb2-A represents the internal image of VP7.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, the absence of cross-reaction among the idiotypic regions of the three anti-VP7 mAbs should not be surprising since a low incidence of cross-reacting Ids was found among mAbs directed to the same antigenic site but derived from different fusions (26). It was interesting to note that both RAb2-B1 and RAb2-B2 reacted strongly with M1877 response to the original antigen, which has been demonstrated in numerous antibody systems (5,7,8,14,15,17,21,22,24,25,28,29). Our observation that immunization of mice with RAb2-A induced an anti-VP7 antibody response further supports the conclusion that RAb2-A represents the internal image of VP7.…”
Section: Discussionmentioning
confidence: 78%
“…Anti-idiotype (anti-Id or Ab2) immunizations for HV (Kennedy et al , 1984; Gurish et al , 1988; Tsuda et al , 1992; Zhou and Afshar, 1995), and BHV-1 in particular have been reported. Srikumaran et al (1990), Hariharan et al (1991), and Orten et al (1991) used neutralizing murine MAb as Ab1 to generate bovine polyclonal Ab (PAb), bovine MAb, or rabbit PAb Ab2 respectively, which in turn were used to elicit neutralizing Ab3 in mice.…”
Section: Vaccinationmentioning
confidence: 99%